Exterior view of a Tudor style house. - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows an exterior view of a house in the Tudor style. The house is situated on the corner, and the far left side hedges line the property. Smaller hedges and plants are visible on the front of the property, and the lawn is well groomed.